2015
DOI: 10.3390/sports3040346
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Progressive Withdrawal of Physiological Protections against High-Intensity Exercise-Induced Fatigue during Puberty?

Abstract: Puberty is characterized by a large number of physiological modifications that translate into increased neuromuscular fatigue during high-intensity exercise in adolescents compared to prepubertal children. This greater neuromuscular fatigue in adolescents could be attributed to peripheral (i.e., muscular) and central (i.e., nervous) factors that change through puberty. Among the peripheral changes are muscle mass, fiber type composition, energy metabolism and musculo-tendinous stiffness. Among the central modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
3
13
0
Order By: Relevance
“…It is also possible that the higher force output in boys results in a higher strain per muscle fiber, which could induce greater muscle damage and lead to more severe symptoms in boys than girls. Previous studies have shown (Falk et al, 2009 ; Dotan et al, 2012 ; Ratel and Martin, 2015 ) that children are less able to recruit or fully utilize their higher-threshold motor units during maximal voluntary isometric contractions of the elbow flexors and extensors when compared with adults. However, further studies are required to compare pre-pubescent, pubescent and post-pubescent males and females for the magnitude of muscle damage by using the same eccentric exercise protocol to examine when sex difference in muscle damage starts to become evident, if sex difference exists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the higher force output in boys results in a higher strain per muscle fiber, which could induce greater muscle damage and lead to more severe symptoms in boys than girls. Previous studies have shown (Falk et al, 2009 ; Dotan et al, 2012 ; Ratel and Martin, 2015 ) that children are less able to recruit or fully utilize their higher-threshold motor units during maximal voluntary isometric contractions of the elbow flexors and extensors when compared with adults. However, further studies are required to compare pre-pubescent, pubescent and post-pubescent males and females for the magnitude of muscle damage by using the same eccentric exercise protocol to examine when sex difference in muscle damage starts to become evident, if sex difference exists.…”
Section: Discussionmentioning
confidence: 99%
“…However, this has not been investigated in previous studies. It is interesting to examine whether eccentric exercise affects PS and JRA differently between different age groups, since impairment of proprioception potentially results in severe injury, especially during the rapid growth period (Ratel and Martin, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review by Ratel and Martin (24) suggest that there may be a progressive withdrawal of physiological protection against high intensity exercise induced fatigue during puberty. However, the authors are cautious as they conclude that the effects of fatigue on neuromuscular function during adolescence has scarcely been studied, despite this knowledge being able to contribute to the management of training load and recovery in maturing children (24). Data on the effects of muscle fatigue on the H/QFUNC in adults is sparse and no studies appear to have calculated the H/QFUNC using functionally relevant procedures (4).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified that fatigue is a significant contributor to reduced lower limb dynamic knee stability, which may increase the risk of non-contact ACL injury [19]. A recent review by Ratel and Martin [29] suggest that there may be a progressive withdrawal of physiological protection against high intensity exercise induced fatigue during puberty. However, the authors are cautious as they conclude that the effects of fatigue on neuromuscular function during adolescence has scarcely been studied, despite this knowledge being able to contribute to the management of training load and recovery in maturing children [29].…”
Section: Introductionmentioning
confidence: 99%